(untitled) (Research, Society and Development, 2025)
Acute Chagas Disease (ACD) constitutes an important public health challenge in the Amazon region, especially in the State of Pará, where oral transmission has become the main route of infection. The expansion of the artisanal açaí production chain and the interaction between environmental, socioeconomic, and cultural factors have contributed to the persistence and territorial spread of the disease. In this context, understanding the epidemiological dynamics of ACD is essential to support prevention strategies. This study aimed to analyze the epidemiological profile of ACD cases reported in the State of Pará, Brazil, between 2015 and 2023. Secondary data from the Notifiable Diseases Information System (SINAN/DATASUS) were used, including all ACD cases (ICD-10: B57.0) reported during the study period. The variables analyzed covered sociodemographic, clinical, and epidemiological aspects. A total of 20,612 ACD cases were recorded. Males were predominant (52.5%), with higher incidence among mixed-race individuals (84.4%) and low education levels. Oral transmission was the main epidemiological antecedent (77.6%), and the municipalities of Abaetetuba, Belém, and Cametá accounted for more than 40% of notifications. Most cases evolved to cure (79.1%), and lethality was low (0.2%). ACD remains an important public health problem in Pará, mainly associated with oral transmission. The results highlight the need to strengthen epidemiological and sanitary surveillance, improve control of regional food production chains, and invest in health education and early diagnosis.